2016
DOI: 10.30659/odj.2.2.4-10
|View full text |Cite
|
Sign up to set email alerts
|

CARIES STATUS EARLY CHILDHOOD CARIES IN INDONESIAN CHILDREN WITH SPECIAL NEEDS : Study In SDLB Central Java

Abstract: Background: The prevalence of ECC (Early Childhood Caries) is still problem in Indonesian, especially in children with special needs. Unstable economic development leads to a poorer economic situation and may have an impact on increasing the prevalence of ECC. This study aimed to investigate the Caries Status of ECC in children with special needs and its association with VRFLRGHPRJUD¿ DQG SDUHQWDO VRFLRHFRQRPLF FLUFXPVWDQFHV LQ 6HPDUDQJ Central Java, Indonesian. Method: This research was conducted in SDLB usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…However, to be successful in SNC, they need their parents to accompany and guide them in tooth brushing activities. [17][18][19] The advantages of tooth brushing training are that it will be easier for children to imitate what they see and then imitate it. 20 Research by Sujarwati (2019) found that tooth brushing skills in mental retardation children before their parents trained was at a minimum score 16 and a maximum 24.…”
Section: Mechanical Cleaning Of Teeth By Tooth Brushing Ismentioning
confidence: 99%
“…However, to be successful in SNC, they need their parents to accompany and guide them in tooth brushing activities. [17][18][19] The advantages of tooth brushing training are that it will be easier for children to imitate what they see and then imitate it. 20 Research by Sujarwati (2019) found that tooth brushing skills in mental retardation children before their parents trained was at a minimum score 16 and a maximum 24.…”
Section: Mechanical Cleaning Of Teeth By Tooth Brushing Ismentioning
confidence: 99%
“…Perhatian akan perawatan gigi rendah disebabkan seseorang tersebut memiliki pengetahuan yang kurang. (Rompis, 2016;Christiono, 2015;Purwati, 2017) Pelaksanaan PKM yang dilaksanakan melalui pelatihan KAPORAGI FKG ULM sebagai upaya dalam pelaksanaan penanggulangan gigi berlubang bagi masyarakat di pinggiran Sungai Barito Kalimantan Selatan memiliki kelebihan dapat membantu menjaring anak usia dini/balita yang memiliki karies gigi melalui pelatihan pengisian odontogram gigi dan mulut anak usia dini 2-5 tahun. Odontogram tersebut dapat dilakukan pengisian pada saat pelaksanaan kegiatan Posyandu setiap bulan, hasil pengisian odontogram terebut dapat disertakan pada Kartu Menuju Sehat (KMS) masing-masing anak sehingga dapat dilaporkan kepada Puskesmas terdekat agar permasalahan Kesehatan mulut dan gigi dapat terdeteksi dan segera tertangani.…”
Section: Gambar (O) Penggumpulan Hasil Kuesioner Oleh Tim Pkm Fkg Ulmunclassified
“…54 Working mothers have less time for their children, but earn an income that can help increase knowledge, including dental and oral health. 55 The income can also meet the needs of prevention and treatment in health. 54 .…”
Section: Introductionmentioning
confidence: 99%